Early Childcare Duration and Students' Later Outcomes in Europe - Daniela Del Boca; Chiara Monfardini; Sarah Grace See (Center for Economic Studies and ifo Institute (CESifo), 2022)
The importance of investment in early childhood education (ECE) has been widely documented in the literature. Among the benefits, particularly for children from disadvantaged backgrounds, is its potential to mitigate educational inequality. However, some evidence also suggests that the positive effects of ECE on later outcomes tend to dissipate over time, leaving children who attended such programmes no better off academically than those who did not. This paper studies the relationship between students' years spent in ECE and the results of their educational assessment outcomes at age 15.Using PISA survey data for fourteen European countries from 2015 and 2018, we conduct a cross-country comparison of student performance in reading, mathematics, and science, correlating the results to early childcare and pre-primary school attendance. Our findings show that participation in early childcare is associated with better assessments at age 15, but that the benefit is nonlinear and peaks at 3-4 years of childcare attendance. Examination of gender heterogeneity patterns reveals differences in girls' and boys' performance on the assessments; however, there are no gender differences in the relationship between childcare participation and test outcomes. We also explore differences related to the type of educational system attended and find distinct results for the unitary and separate settings.
Keywords: I20; J13; J16; 330; early childhood education; pre-primary; early investments; human capital; assessments; gender; institution; unitary; separate; PISA